Digitalization During a Pandemic - Shotarov, Antoan (Research Papers, 2021)
In 2020 the global pandemic caused by COVID-19 led to economic and social problems with great impact. Even more important, the pandemic resulted in the loss of millions of lives. The world’s economy shranked with enormous size in 2020 and many countries currently face recession. It is not easy to be found fields and processes which COVID-19 has had impacted positively, but the analyze of concrete researches shows that one of them is digitalization. The pandemic accelerated the process which put to a test both private and public sector.